Efficacy Of Calcium Supplementation And Weightbearing Exercise On Bone Mineral Density In Postmenopausal Chinese Women - Chan, Yoke Mun (2003)
The etiology of age-related bone loss is unclear but both habitually low calcium intake and lack of physical activity have been proposed as its determinants. The objective of this two-year randomized controlled trial was to evaluate the efficacy of increasing calcium intake and weight-bearing exercise on bone mineral density (BMD) in postmenopausal Chinese women who were not on hormone replacement therapy. Bone mineral density at the total body, lumbar spine L2-L4, femoral neck, Ward's triangle, trochanter and total hip were measured using dual energy X-ray absorptionmetry (DEXA) at six month intervals. Information on sociodemographic background, lifestyle factors and reproductive history were assessed using a validated questionnaire. Calcium intake was evaluated by both the three-day food record and food frequency questionnaire at baseline, 1 2 and 24 months. Exercise habits were assessed with an exercise diary and Physical Activity Scale for the Elderly (P ASE) questionnaire.